Efektivitas Bahasa Empatik terhadap Kualitas Relasi Terapeutik antara Dokter dan Pasien Geriartri: Tinjauan Literatur - Desliani; Jonathan William Salomo; Perawati (Journals of Indonesian Multidisciplinary Research, 2025)
The increasing number of elderly people in Indonesia demands improved quality of geriatric care, particularly in communication, where empathetic communication plays a key role in building a strong therapeutic relationship between doctors and elderly patients. This study is a literature review that aims to evaluate the effectiveness of empathic language on the quality of therapeutic relationships in the context of geriatric services. Articles were selected through an identification and screening process using specific keywords in databases such as Sinta, Neliti, Garuda, and Google Scholar, with inclusion criteria that include studies in the last 10 years, in Indonesian or English, full-text, and are primary research. The results show that empathic communication through cognitive and affective empathy plays a significant role in increasing patient trust, adherence to treatment, and clinical and psychosocial outcomes, such as decreased anxiety and increased quality of life. Communication strategies include the use of simple language, personal attention, and consistent emotional engagement. Implementation barriers include high workload and a lack of training. Empathy training in medical curriculum, the development of patient-centered communication guidelines, and the holistic implementation of the Comprehensive Geriatric Assessment (CGA) are essential.